Effect of dopants on the electrocaloric effect of 0.92 Pb(Mg1/3Nb2/3)O3–0.08 PbTiO3 ceramics. Issue 7 (July 2015) - Molin, C.; Sanlialp, M.; Shvartsman, V.V.; Lupascu, D.C.; Neumeister, P.; Schönecker, A.; Gebhardt, S.
Abstract: This paper presents an extract of modifications of lead magnesium niobate–lead titanate in order to optimize its electrocaloric properties. Electrocaloric entropy (Δ S EC ) and temperature changes (Δ T EC ) are measured in a temperature range from −5 °C up to 100 °C using differential scanning calorimetry. The influence of dopants (Li +, Mn 2+, Sr 2+, Ta 5+ ) on the electrocaloric effect as well as on microstructure, dielectric and ferroelectric behavior is investigated. The maximum of relative permittivity can be shifted to lower or higher temperatures depending on the added dopant and decreased ferroelectric hysteresis losses were observed for all altered compositions. For the undoped PMN–8PT ceramics maximum Δ T EC of 0.58 K and Δ S EC of 0.51 J kg −1 K −1 were measured, when applying an electric field of 2 kV mm −1 at 30 °C. The electrocaloric temperature change showed lower values for all doped PMN–8PT. Remarkably, this is accompanied with an increase of the entropy change for the Li-doped sample.